2016
DOI: 10.1111/maps.12593
|View full text |Cite
|
Sign up to set email alerts
|

Tenoumer impact crater, Mauritania: Impact melt genesis from a lithologically diverse target

Abstract: Abstract-Impact melt rocks from the 1.9 km diameter, simple bowl-shaped Tenoumer impact crater in Mauritania have been analyzed chemically and petrologically. They are heterogeneous and can be subdivided into three types based on melt matrix color, occurrence of lithic clast components, amount of vesiculation (melt degassing), different proportions of carbonate melt mingled into silicate melt, and bulk rock chemical composition. These heterogeneities have two main causes (1) due to the small size of the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…; Schultze et al. ). Specifically, it has been shown that they are the result of mixing of not less than six different target components in variable proportions, that is, 50% granitoids, 17–19% mica schist, 15% amphibolite, 10% limestone, and 6% ultrabasite (Pratesi et al.…”
Section: Geological Background Related To the Natural Samples And Expmentioning
confidence: 98%
See 4 more Smart Citations
“…; Schultze et al. ). Specifically, it has been shown that they are the result of mixing of not less than six different target components in variable proportions, that is, 50% granitoids, 17–19% mica schist, 15% amphibolite, 10% limestone, and 6% ultrabasite (Pratesi et al.…”
Section: Geological Background Related To the Natural Samples And Expmentioning
confidence: 98%
“…The most recent age determination is that of Schultze et al. (), who obtained a weighted mean age of 1.57 ± 0.14 Ma by 40 Ar/ 39 Ar step‐heating analysis of three impact melt rock samples.…”
Section: Geological Background Related To the Natural Samples And Expmentioning
confidence: 99%
See 3 more Smart Citations